THE ABILITY OF SECOND SEMESTER STUDENTS OF ENGLISH LITERATURE STUDY PROGAM IN IDENTIFYING NOUN AND VERBS IN SHORT STORY "THE STORY OF GOLDILOCKS AND THE THREE BEARS" AND "A PLATE OF HOT RICE" - Maisya, Aila; Andriani, Nia; Eka N, Oktavia; Rahmawati, Wina; Rullyanti, Merry (Journal Albion : Journal of English Literature, Language, and Culture, 2023)
ABSTRACTThe title of this research is "The Ability of Second-Semester Second-Semester Students of English Literature Study Program to Identify Nouns and Verbs in Short Stories "The Story of Goldilocks and the Three Bears" and "A Plate of Hot Rice". The purpose of this study is to evaluate the ability of second semester second semester students in displaying nouns and verbs in several sentences in short stories. The method used in this research is quantitative method by using cross sectional approach. The results showed that most of the second semester students had a fairly good ability to show verbs in sentences. Furthermore, related to the ability to show nouns, the results showed a significant improvement compared to the ability to show verbs. the findings of this study indicate that second semester English literature students have a relatively good ability to show verbs and nouns in sentences. However, there is still room for improvement and enhancement of their understanding.